Birds of the state of Tocantins, Brazil: checklist of species and synthesis of knowledge - Dornas, Tulio; Marcelino, Dianes Gomes; Dantas, Sidnei de Melo; Pinheiro, Renato Torres; Pacheco, José Fernando; Prado, Advaldo Dias; Aleixo, Alexandre; Corrêa, André Grassi; Buzzetti, Dante; Rodello, Déborah; Lopes, Divino Nunes; Olmos, Fábio; et al. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2024)
The first synthesis related to the avifauna of the state of Tocantins resulted from the ornithological collections conducted by José Hidasi, between the 1960s and 1990s, with the Tocantins bird records being compiled again in 2009. After 15 years and a significant increase in ornithological studies in Tocantins, we present a new list of bird species occurring in the state, considering richness and composition, migratory status, endemism, conservation status and biogeographical aspects. In all, 720 species were listed, of which 699 (97%) have documentary evidence of occurrence in Tocantins (primary list), while 21 species (3%) were sighted and/or heard (secondary list). This total represents 36,6% of the recognized avifauna for Brazil. Another 55 species were discarded for Tocantins (tertiary list). Still referring to the total of 720 species, 48 are considered endemic to Brazil, 30 are Nearctic continental migrants and five are southern migrants, while 43 species are classified as threatened globally or nationally. The occurrence in sympatry of typical elements of the avifauna of the Amazon and the Cerrado reflects the ecotonal character of the avifauna of the state, which is occasionally home to species typical of the Caatinga and Atlantic Forest, and anticipates the future description of a presumably new species of the genus Certhiaxis. To conclude, the list is presented as an initial basis for creating a state list of endangered birds.
Keywords: Birds of the Cerrado; Birds of the Amazon; Biodiversity; Ecotone; Tocantins avifauna